Association of serum iron and hepcidin levels with stroke from 1990 to 2022: A systematic review and meta-analysis. (May 2023) - Wang, Lizhi; Miao, Yuxi; Ma, Zitai; Jiang, Wenjuan; Zhou, Jing; Lv, Junya; Ren, Jie; Liu, Mingyan; Du, Ke
Graphical abstract: Highlights: Stroke patients had significantly higher serum iron and hepcidin levels compared with healthy controls. Hepcidin level is associated with the degrees and prognosis of stroke. Iron and hepcidin may be prognostic markers and therapeutic targets in stroke patients. Abstract: Iron widely exists in minerals and food, and has an essential role in human health. A major iron-regulating peptide hormone, hepcidin, maintains the balance of iron metabolism. The association between serum iron, hepcidin levels, and stroke risk is still under ongoing research. In this meta-analysis, Random‐effects meta‐analysis revealed that stroke patients had significantly higher serum iron and hepcidin levels compared with HC subjects. Further analysis of serum hepcidin levels in different degrees of stroke and its relation to prognosis revealed that hepcidin level is also associated with the degrees and prognosis of stroke. Finally, the role of iron overload in the mechanism of stroke development and the effect and mechanism of iron chelator intervention in stroke were also reviewed. Overall, the findings indicate that stroke patients had higher serum iron and hepcidin levels compared with healthy subjects, and their changes were associated with the severity and prognosis of stroke.